Peningkatan Hasil Pembelajaran Tematik Menggunakan Model Discovery Learning di Sekolah Dasar - Feby Kurniawan; Yeni Erita; Didi Syahril; Vani Qhairumnisa Utami (Departement of Mathematics Education, 2023)
Successful learning can be interpreted as the achievement expected by students, such as the abilities obtained or the grades achieved, in the learning process. According to (Somayana, 2020) the achievement of student learning outcomes can be measured through exams and assignments they complete, as well as through active participation in asking and answering questions that support the learning process. This type of research is classroom action research (PTK) using qualitative and quantitative approaches. This research was conducted in two cycles. Each cycle consists of planning, implementing, observing, and reflecting. The results of the first cycle of research obtained an average percentage value of 80.12% with a good qualification, increased in cycle II to 92.85% with a very good qualification. Implementation of the first cycle on teacher activities obtained an average percentage value of 82.81% with a Good qualification, increased in cycle II to 96.87% with a Very Good qualification. The implementation of the first cycle in student activities obtained an average percentage value of 82.81% with a Good qualification, increasing in cycle II to 96.87% with a Very Good qualification. While the learning outcomes of students in cycle I with a final score of 78.05 increased in cycle II with an acquisition of 93.32. Thus, it can be concluded that the Discovery Learning learning model can improve integrated thematic learning outcomes in grade V Elementary School.